Selective intra-operative parathyroid hormone in re-do neck exploration in parathyroidectomy: A case report. (2019) - To, Henry; Otto, Gregory
Highlights: Intra-operative parathyroid hormone (I-OPTH) measurement is essential in challenging cases, where there has not been localisation of the hyperfunction gland/s and/or redo neck surgery. The difficulty of the case is compounded by these factors. Appropriate methodology is required to perform and interpret I-OPTH, which includes specific and consistent location of sampling (ipsilateral internal jugular vein), and application of verified protocols. Appropriate use of I-OPTH can reduce operative time, cost and complications. Abstract: Introduction: Intra-operative parathyroid hormone (I-OPTH) levels are an adjunct used in parathyroid surgery which provides assurance that parathyroidectomy surgery is complete and has removed the hypersecreting gland. Presentation of case: A 78 year old female with no localisation on pre-operative imaging and had previous hemithyroidectomy. I-OPTH was used to guide the side and timing for completion of exploration, factors which reduced operative time, operative cost and avoided potential complications. Discussion: Routine and selective I-OPTH may be used to guide parathyroidectomy, and this case highlights the methodology of use in a selective challenging case. Appropriate application and interpretation of results must be achieved to ensure adequate completion of surgery and cure for the patient. Conclusion: Selective use of I-OPTH guides parathyroidectomy in challenging cases, and can be time and cost-effective when used appropriately.